Changing roles of agricultural economics - Hussein, Mohd. Ariff (Universiti Pertanian Malaysia, 1994)
Not many years ago universities around the world were generally the most pampered institutions on earth. Governments showered them with money. They were seen by right wing governments as engines of economic growth, by left wing governments as engine of social equality, and by citizens in general as avenues of social mobility. Economists such as Lionel Robbins had argued that universities have discovered the secret of growth; the more a society invested in higher education, the faster the economy grew, the faster its economy grew, the more it could invest in higher education.